Serum sclerostin levels in patients with non-dialysis chronic kidney disease - Vo, Thi Hoai Huong; Nguyen, Hoang Thanh Van; Phan, Thi Minh Phuong (Tạp chí Y Dược Huế, 2025)
Objective: 1) To evaluate the serum sclerostin concentration in patients with CKD who have not yet undergone dialysis from stage G3 to G5, compared with a control group of healthy people with normal renal function. 2) To evaluate the relationship between serum sclerostin concentration and some related factors in patients with CKD. Patients and methods: This is a cross-sectional descriptive study on 84 patients with CKD who have not yet undergone dialysis (including 32 patients with stage 3, 4 CKD and 52 patients with stage 5 CKD) at the Department of Nephrology - Musculoskeletal, Hue Central Hospital and 60 healthy people with normal kidney function regularly came for health check-ups at the Internal Medicine Clinic of Hue University of Medicine and Pharmacy from April 2023 to 2025. Results: Our study was conducted on 84 non-dialyzed patients with chronic kidney disease (CKD) stages 3 to 5, including 32 patients in stages 3 and 4, and 52 patients in stage 5. The control group consisted of 60 healthy individuals with normal renal function. The mean serum sclerostin concentration in the control group was 359.52 ± 168.21 pg/mL. Serum sclerostin levels were significantly higher in the CKD group compared to controls (p < 0.05), with levels in the CKD stage 3–4 group recorded at 1090.63 ± 901.65 pg/mL and in the stage 5 group at 1464.26 ± 892.94 pg/mL. In our study, serum sclerostin levels were significantly higher in males than in females within the control group (p < 0.05) and in the CKD stage 5 group. Furthermore, serum sclerostin levels showed a statistically significant positive correlation with age in the CKD stage 3–4 group (p < 0.05). No statistically significant differences in serum sclerostin concentrations were observed between non-dialyzed CKD patients with or without hypertension or anemia. Conclusion: Sclerostin is a glycoprotein produced by osteocytes that inhibits bone formation through the Wnt/β-catenin signaling pathway. In patients with CKD, serum sclerostin levels progressively increase with advancing stages of the disease. Our study demonstrated that in non-dialyzed CKD stage 3 - 5 patients, serum sclerostin levels were significantly higher than in healthy controls with normal renal function. According to our findings, serum sclerostin concentrations were higher in males than in females in both the control group and in patients with CKD stage 5, and levels tended to increase with age. However, no statistically significant differences in serum sclerostin levels were observed between non-dialyzed CKD patients with or without hypertension or anemia.